1994
DOI: 10.1063/1.112480
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Raman scattering and spectral ellipsometry on InAs/GaSb superlattices with different interfaces

Abstract: We have used Raman spectroscopy and spectral ellipsometry to investigate InAs/GaSb short-period superlattices (SLs), grown by molecular-beam epitaxy, with either InSb- or GaAs-like interfaces. Room-temperature ellisometric measurements show spectral features in the dielectric function due to the E1 and E1 plus Delta1 interband transitions of GaSb and InAs. For SLs with small InAs layer thickness (4 ML InAs/10 ML GaSb) the critical point energies are found to depend on the type of interfacial bonding, with an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…[22] An attempt has been made to perform the cleaved edge Raman study on the T2SL, but failed to resolve the SL signal from that of the substrate. [21] In short, except for the IF modes, previous efforts on the T2SL have not been able to make any unambiguous connection between the experimental results and the theoretical predictions.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…[22] An attempt has been made to perform the cleaved edge Raman study on the T2SL, but failed to resolve the SL signal from that of the substrate. [21] In short, except for the IF modes, previous efforts on the T2SL have not been able to make any unambiguous connection between the experimental results and the theoretical predictions.…”
mentioning
confidence: 86%
“…[17][18][19][20][21][22][23][24] Most of them were performed in the (001) back-scattering geometry, with only one major Raman peak observed at around 236 238cm -1 assigned generally as a SL-LO mode. It was believed that the overlapping of the bulk phonon modes would make it difficult to resolve the confined and extended modes.…”
mentioning
confidence: 99%
“…It is anomalous that a blue shift peak is corresponding to InAs E 1 and GaSb E 1 + Δ 1 . D. Behr et al reported that it is complicated by inhomogeneity for E 1 and transition of InAs and E 1 + Δ 1 of GaSb [14]. …”
Section: Resultsmentioning
confidence: 99%
“…All samples with shutter sequence A With Raman spectroscopy one can gain information on the nature and type of the different interfaces. In [5] we could identify the different interfaces in InAs/GaSb superlattices. Using different polarizations we could even differentiate between upper and lower interfaces.…”
Section: Mbe Growthmentioning
confidence: 99%